EXPERIMENT ON COLD-FORMED STEEL C-SECTION JOINT WITH SCREW AND ADHESIVE MATERIAL - Komara, Indra; Taşkin, Kıvanç; Wahyuni, Endah; Suprobo, Priyo (MATTER: International Journal of Science and Technology, 2017)
Experiments were performed on the cold-formed steel C-section (CFS-CS) joints using the screw and adhesive material as the main subject of the study to assess the tensile stress-strain capacity. Since the connection has become the foremost aspect of the CFS-CS structure, a number of studies have been focusing to provide a better understanding with regard to the behavior of the connection. Even more so, further studies have also been carried out focusing on alternate solutions to improve the connection capacity. Considering all the above, this paper discusses the influence of varying types of connection on the tensile behavior of CFS-CS elements with particular using the self-drilling screw and 3M Scotch-weld DP810 as an adhesive material. The configurations of the screw(s) used in this study were 1, 2, and 3, while the percentages of adhesive material being used were 50%, 75%, and 100%. The results showed that the use of a higher amount of adhesive does not significantly increase the load capacity, but alleviate the failure condition. The results also showed that all test specimens satisfy the minimum requirement according to design specifications.